PEMBERHENTIAN BUPATI GARUT DALAM PERSPEKTIF FIKIH SIYÄ€SAH AL-MAWARDI - Irfan, M Nurul (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2014)
This article intends to analyze the case of Garut Regent dismissal, Aceng Fikri from his position according to al-Mawardiâ€™s Fiqh Siyasah perspective. Reasons for the dismissal Â was a violation of Article 28 f Â UU No. 32 / 2004 on Regional Government. The article states that the head of regional and the deputy of head of regional are prohibited from misusing authority and violation of the oath of position. In addition, he is also considered not to meet the obligation for local office as mentioned in Article 27 point (1), letter e, which is the regional head and deputy regional head has the obligation to obey and enforce all laws and regulations. In the perspective of Fiqh Siyasah al-Mawardi, an unfairly leader can dismissed from his post. One indicator of an injustice leader is a violation of ethics.